2020
DOI: 10.3390/bs10070114
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Past Bonding Experience with Their Parents Interacts with Current Parenting Stress to Influence the Quality of Interaction with Their Child

Abstract: Healthy dyadic interactions serve as a foundation for child development and are typically characterised by mutual emotional availability of both the parent and child. However, several parental factors might undermine optimal parent–child interactions, including the parent’s current parenting stress levels and the parent’s past bonding experiences with his/her own parents. To date, no study has investigated the possible interaction of parenting stress and parental bonding history with their own parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…Furthermore, and in line with the literature that highlights a strong interdependence between children and their caregivers during early childhood (Azhari et al., 2020; Ponnet et al., 2013), the results show a positive correlation between parents’ perception of the deterioration of their own daily functioning and their children's daily functioning. This association could lead to a negative judgement of children's functioning starting from parents' own discomfort or the impact of children's symptoms on their parents.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, and in line with the literature that highlights a strong interdependence between children and their caregivers during early childhood (Azhari et al., 2020; Ponnet et al., 2013), the results show a positive correlation between parents’ perception of the deterioration of their own daily functioning and their children's daily functioning. This association could lead to a negative judgement of children's functioning starting from parents' own discomfort or the impact of children's symptoms on their parents.…”
Section: Discussionsupporting
confidence: 90%
“…When arriving at this conclusion, it is important to rule out confounding factors such as differences in parenting and child behaviours across dyads with greater compared to lesser parenting stress that could have driven the positive association between inter-brain synchrony and parenting stress. In our previous behavioural analyses study that examined parental and child aspects of emotional availability during play using this same dataset [23], we showed that there was no significant relationship between total parenting stress and parental sensitivity, structuring, intrusiveness, hostility as well as child responsiveness and involvement during play. As such, differences in Parent-Child Dyads with Greater Parenting Stress Exhibit Enhanced Inter-brain Synchrony parenting and child behaviours across high-and low-stressed dyads were not driving the positive correlation between synchrony and parenting stress.…”
Section: Discussionmentioning
confidence: 81%
“…For the co-viewing chapter where dyads watched animation shows together, studies investigating the link between psychological variables (e.g., parenting stress, attachment, gender differences) and parent-child brain activity have been published [53][54][55][56]. For the play chapter, a behavioural study has been published on the association between parenting stress, past bonding experiences and parentchild emotional availability [23], while a technical paper has been published to determine optimal methodical strategies and parameters when computing inter-brain synchrony in interactional paradigms [48]. The present study examines parenting stress in relation to inter-brain synchrony during joint and non-joint segments of mother-and father-child shared play.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the attachment theory [ 25 ], adult individuals use their early experiences of attachment during infancy as a reference for their social relationships. Different attachment styles have been proven to affect, for example, the perception of others’ pain [ 26 ], the quality of interaction with their children [ 27 ], as well as the perception of complex emotional scenes [ 28 ].…”
Section: Introductionmentioning
confidence: 99%